2017
DOI: 10.1097/dcr.0000000000000789
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Anastomotic Leak in Elderly Patients After Colectomy: Nomogram-Based Assessment From the American College of Surgeons National Surgical Quality Program Procedure-Targeted Cohort

Abstract: An accurate prediction of anastomotic leak affecting morbidity and mortality after colorectal surgery using the proposed nomogram may facilitate decision making in elderly patients for healthcare providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 20 publications
3
51
1
1
Order By: Relevance
“…In some instances conclusive recommendations are firmly justified whereas others are still open to debate[ 1 , 10 ]. Many authors have tried to compose nomograms in order to predict the risk of AL yet, despite the significance of such scores, they are not frequently used in clinical practice[ 11 - 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some instances conclusive recommendations are firmly justified whereas others are still open to debate[ 1 , 10 ]. Many authors have tried to compose nomograms in order to predict the risk of AL yet, despite the significance of such scores, they are not frequently used in clinical practice[ 11 - 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies comparing OC and MIS approaches for anastomotic leaks show inconsistent results, with one study suggesting there are fewer leaks with both RC and LC approaches compared with the OC approach. 16 …”
Section: Discussionmentioning
confidence: 99%
“…It may be that the sample size in our study is so large that the statistically significant difference in these rates is not clinically different for this complication. 3 , 4 , 8 , 16 Anastomotic leak rates are associated with several risk factors that are difficult to control for in statistical models. The reasons for inconsistent results in studies to date are not apparent at this time, and definitive conclusions based on these results would be difficult to determine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they concluded that in selected patients, an emergency left-colon, 1-stage resection and primary anastomosis might be performed without colonic preparation as safely as elective surgery. On the other hand, Rencuzogullari et al [5] recently reported the database review of the American College of Surgeons National Surgical Quality Improvement Program to determine predictors of anastomotic leak in elderly patients undergoing a colectomy. They found that the omission of MBP was deleterious in terms of surgical site infection, anastomotic dehiscence, ileus, length of hospitalization, and even recurrence of the neoplasm when compared to colon surgery with MBP, especially when (in the American studies) MBP was combined with oral antibiotic administration.…”
mentioning
confidence: 99%